الكفايات التعليمية الأساسية ومدى توافرها لدى معلمات رياض الأطفال دراسة ميدانية في مدينة اللاذقية - ميلاد محمود; بدور سماح محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث إلى تعرف درجة توافر الكفايات التعليمية الأساسية لدى معلمات رياض الأطفال في مدينة اللاذقية, ودراسة الفروق بين المعلمات في درجة توافر الكفايات تبعاً لمتغيرات(المؤهل العلمي، سنوات الخبرة، عدد الدورات التدريبية التي التحقت بها معلمة الروضة). اعتمدت الدراسة على المنهج الوصفي التحليلي، وذلك لملاءمته مع طبيعة الدراسة وإجراءاتها،, وتمّ بناء بطاقة ملاحظة من (56) عبارة, وأجريت الدراسة على (54) معلمة من معلمات رياض الأطفال سحبت باستخدام العينة العشوائية البسيطة, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: 1-تتمتع معلمة الروضة بقدرٍ وافٍ من الكفايات الشخصية التي تجعلها قادرة على التعامل مع الأطفال بشكل يرقى بهم إلى مستوى مقبول, ويحقق لهم النمو المتوازن والمتكامل. 2- تعاني معلمات الروضة من ضعف في بعض الكفايات التعليمية وخاصة تلك المتعلقة بأساليب التقويم, وصياغة الأهداف التعليمية, وربط الأهداف الخاصة بالأهداف العامة, واستخدام الأجهزة والوسائل التعليمية, وتصميم الأساليب التعليمية, وتحديد مجالات الأهداف (معرفي, نفس حركي, وجداني), ويعود الضعف في توافر بعض الكفايات التعليمية إلى قلة التدريب, وعدم استخدام الأساليب والوسائل التعليمية الحديثة, ونقص في الإعداد الأكاديمي وخصوصاً أن نسبة كبيرة من أفراد العينة يحملون مؤهلات علمية غير تربوية. 3- وجود فروق ذات دلالة إحصائية بين معلمات الروضة في مدى توافر الكفايات التعليمية تبعاً لمتغيرات المؤهل العلمي, وسنوات الخبرة, وعدد الدورات التدريبية. The research aims to identify the degree of availability of basic educational skills of kindergarten teachers in the city of Latakia, and study the differences between the parameters in the availability of skills depending on variables of (qualifications, years of experience, the number of courses you have attended kindergarten teacher). The study relied on descriptive analytical method, because of its relevance to the nature of the study and its procedures. A card note of (56) words was built, and the study was conducted on (54) teachers of kindergarten pulled using simple random sample, and after the study and analysis, we reached the following results: The kindergarten teachers have an adequate personal skills that make them able to deal with their children which amounts to an acceptable level, and bring them balanced and integrated growth. Teachers suffer of weakness in some educational competencies, especially those relating to the methods of straightening, the formulation of educational goals, tying goals for the overall objectives, and the use of devices and teaching aids, design teaching methods, and identify areas for goals (cognitive, same motor, and emotional). This weakness in the availability of some educational competencies goes back to lack of training, not using modern methods and teaching aids, and a lack of academic preparation and especially that a large proportion of respondents hold non-educational qualifications. There were statistically significant differences between the parameters kindergarten in the availability of educational competencies according to the variables of qualification, years of experience, and the number of training courses.